Ultraviolet radiation oxidative stress affects eye health. Issue 7 (24th April 2018) - Ivanov, Iliya V.; Mappes, Timo; Schaupp, Patrick; Lappe, Christian; Wahl, Siegfried
Abstract : Ultraviolet radiation role in oxidative stress‐related ocular pathologies is less clear than its role in cancer. Excessive exposure to ultraviolet radiation seriously contributes to increase in oxidative stress in eye tissues, and to the advancement of glaucoma, age‐related macular degeneration, etc. Children are especially vulnerable to large pupils and transparent ocular media. Efficient everyday protection of the eye should be considered from early age. Worldwide initiatives inform and raise awareness about these invisible hazards. Abstract : In the eye, ultraviolet radiation (UVR) is not known to contribute to visual perception but to mainly damage multiple structures. UVR carries higher energy than visible light and high dose exposure to UVR causes direct cellular damage, which has an important role in the development of cancer. This review provides an overview on the most recent knowledge on the role of UVR in oxidative stress (OS) in relation to noncancer ocular pathologies: various corneal pathologies, cataract, glaucoma and age‐related macular degeneration. Possible OS signaling streams and mechanisms in the aging eye are discussed. Excessive exposure to UVR through live may seriously contribute to increase in OS of various eye tissues and thus lead to the advancement of serious ocular pathologies. Children are especially vulnerable to UVR because of their larger pupils and more transparent ocular media: up to 80% of a person's lifetime exposure to UVR is reached before the age of 18. Therefore, efficient everyday protection of the sensitive tissues of the eye by wearing of sunglasses, clear UVR‐blocking spectacles or contact lenses should be considered from early age on. Many initiatives are taken worldwide to inform and raise the population's awareness about these possible UVR hazards to the eye.